The Impact of Alcohol Consumption on Occupational Attainment in England - Ziggy MacDonald; Michael A. Shields (Institute for the Study of Labor (IZA), 2000)
In this study we provide evidence on the effect of alcohol consumption on occupational attainment in England. To do this we use samples of employees from the Health Survey for England between 1992 and 1996. We find that due to the endogenous nature of alcohol consumption, OLS estimates may provide a biased picture of the impact of alcohol consumption on occupational attainment. Using various sets of instrumental variables, we find positive and significant returns to moderate levels of drinking for male and female employees which drop-off rapidly as consumption increases.
Keywords: J24; 330; Alcohol; occupational attainment; endogeneity; Alkoholkonsum; Betriebszugehörigkeit; Arbeitsproduktivität; Lohn; Schätzung; Großbritannien